Would you help me again? The role of moral identity, helping motivation and quality of gratitude expressions in future helping intentions. (October 2022) - Iwai, Tatiana; de França Carvalho, João Vinícius
Abstract: Moral identity has been considered an important predictor of prosocial behavior. This article extends prior research by investigating how and when moral identity predicts helping behavior. Specifically, we examine the mediating effect of episodic autonomous motivation on the relationship between moral identity and future helping intentions. We also test the moderating effect of an important contextual factor in helping episodes: the quality of the gratitude expression received by helpers. In two studies using autobiographical recall tasks with different samples (Study 1: N  = 134, college students; Study 2: N  = 192, adult workers), we found convergent evidence that helpers with high moral identity experience higher autonomous motivation in a helping episode, which in turn increases their willingness to help the same beneficiary in the future. We further found support for the interactive effects between autonomous motivation and gratitude quality on future helping intentions. High-quality gratitude expressions are particularly important in predicting subsequent helping for helpers with low episodic autonomous motivation. In this case, high-quality gratitude expressions can compensate for the lack of intrinsic motivation in a helping episode and increase future help provision. Highlights: Moral identity is a strong predictor of autonomous motivation in helping episodes. Autonomous motivation mediates the effects of moral identity on subsequent helping. Quality of gratitude expressions attenuates the effects of low autonomous motivation in future helping.